Improving Students' Writing Skills through Group Work - Ramauli, Fitri; Subari, Imam; Herlisya, Destia (CV. Tripe Konsultan, 2023)
This research was aimed to improve students' writing skills through group work. The subject of the research were the 11th IPA 7 of SMA Negeri 1 Natar that consisted of 36 students. This research used Classroom Action Research (CAR) which was consisted of two cycles. Collection data technique was used test and non-test. Writing test used to know students’ writing skill. Menwhile, observation sheet and interview for non-test. Data analyzing was used quantitative and qualitative method. Refers to the result of the test, the mean score of students’ learning activities cycle 1 was 6.65 with the criteria was less active. Meanwhile in cycle 2 was 7.57 with the criteria was active. The improvement was 0.92. In the other hand, mean score of writing test in cycle 1 was 60 or 8 students who got score ≥70 with the percentage 22%. Meanwhile, mean of writing test in cycle 2 was 75.57 or 20 students who got score ≥70 with the percentage 55%. The improvement was 33% or 15.57. Based on the result of the research, Group Work can improve students’ writing skill in the 11th IPA 7 of SMA Negeri 1 Natar.